The enemy you gnocchi - Bruns, Catherine (Bruns, Catherine. Italian chef mysteries, 2021)
"It's the holiday season in Harvest Park, and the town is in a flurry of activity leading up to the popular Festival of Lights display! Tessa Esposito, chef and owner of Anything's Pastable, is keeping all things merry, bright, and delicious for everyone. But a dark cloud looms when Mario Russo, the new proprietor of More Mocha, decides it's thyme to sleigh his competition. Mario's new espresso bar has been stealing customers from Java Time, owned by Tessa's beloved friend, Archie. Things go from less-than-jolly to bleak when Mario, dressed up like Santa, is found dead in the snow during the Festival with one of Archie's knives besides him. Suspicion begins to snowball about town, and Tessa knows that it's up to her to prove her friend's innocence - and stop a cold-blooded killer - before it becomes the deadliest time of year ... "--